Penggunaan Video Animasi Dengan Model Pembelajaran Problem Solving Untuk Meningkatkan Kemampuan Bertanya Dan Menyimpulkan - Rahayu, Enok Cucu; Sudin, Ali; Nugraha, Dadan (Jurnal Pena Ilmiah, 2021)
With a problem-solving model, students will gradually grow to be complete, Students will gradually grow to be complete, meaning that student changes do not only occur in cognition but also emotions and mental movements with an internal understanding of the problems at hand. The purpose of this study was to determine the implementation, improvement, and response of students regarding the use of animated videos in elementary school students' learning. . The research was using qualitative descriptive with a homeroom teacher and 4th-grade students that using instruments in the form of documentation, tests, and interviews. There are found several obstacles in the implementation of online learning such as smartphones, quotas, and internet networks. The results from this research, that the use of animated video with the learning model of problem-solving was implemented properly. There was an increased inability in the learning process, students actively asked questions and were able to conclude the material presented. In addition, the students' responses were very good, as seen from their enthusiasm and enthusiasm to ask questions without fear of being wrong and embarrassed. Here it appears that there is a change in a very good direction.